2017
DOI: 10.1007/s12565-017-0401-2
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous inferior mesenteric artery supplying the ascending, transverse, descending, and sigmoid colons

Abstract: We have encountered in our anatomical practice the first case and an extremely rare second case in which the ascending, transverse, descending, and sigmoid colons were supplied by the inferior mesenteric artery. The causes of colic artery anomalies are generally explained in conjunction with the development of the superior mesenteric artery, which is intimately related to embryonic elongation and midgut rotation. However, this embryological model was inapplicable to both cases. This difficulty motivated us to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In the rare case reported here, however, the cranial mesenteric artery only gave rise to the caudal pancreaticoduodenal, jejunal and ileal arteries, whereas the caudal mesenteric artery gave origin to the ileocecocolic, middle colic, right colic, left colic and cranial rectal arteries. Although prior rabbit studies have not reported this untypical branching pattern [2,6,7,9], Abe et al [1] and Covanțev et al [4] reported a similar case in humans, in which the cranial mesenteric artery supplied the proximal small portion of the ascending colon and cecum [1], or cecum only [4] via the ileocecal artery. Furthermore, they also found that the caudal mesenteric artery supplied most of the colon via the right colic, cranial left colic and caudal left colic arteries [1], or via the right colic, middle colic, accessory middle colic, left colic and accessory left colic arteries [4].…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…In the rare case reported here, however, the cranial mesenteric artery only gave rise to the caudal pancreaticoduodenal, jejunal and ileal arteries, whereas the caudal mesenteric artery gave origin to the ileocecocolic, middle colic, right colic, left colic and cranial rectal arteries. Although prior rabbit studies have not reported this untypical branching pattern [2,6,7,9], Abe et al [1] and Covanțev et al [4] reported a similar case in humans, in which the cranial mesenteric artery supplied the proximal small portion of the ascending colon and cecum [1], or cecum only [4] via the ileocecal artery. Furthermore, they also found that the caudal mesenteric artery supplied most of the colon via the right colic, cranial left colic and caudal left colic arteries [1], or via the right colic, middle colic, accessory middle colic, left colic and accessory left colic arteries [4].…”
mentioning
confidence: 88%
“…In humans, several authors have reported rare ramification patterns of the cranial (=superior) and caudal (=inferior) mesenteric arteries [1,4,5,10,16]. For example, Kitamura et al [10] and Yamasaki et al [16] reported cases where the cranial and caudal mesenteric arteries emerged from the abdominal aorta as a common trunk.…”
mentioning
confidence: 99%
See 3 more Smart Citations